Post-Conflict Infrastructure : Trends in Aid and Investment Flows - Schwartz, Jordan; Halkyard, Pablo (World Bank, Washington, DC, 2012)
As war and civil strife subside, can governments turn to the private sector to restore basic services? Post-conflict countries suffer from disproportionately low levels of private investment in infrastructure, with only small-scale service providers likely to emerge during, and right after conflict. Larger investors are slow to enter, and when they do, they focus almost exclusively on the easily secured, and most profitable sub-sectors. Yet, some countries have been able to couple aggressive reform and liberalized policies to attract infrastructure investments soon after conflict abates. What does their experience tell us? This Note summarizes an analysis from a companion paper, and explores policy options for post-conflict countries seeking to attract private investment in infrastructure. It suggests improving the underlying factors influencing political and economic risk ratings, for it may lead to faster growth in infrastructure investment in conflict-affected countries, than in other developing countries.